Developing cultural – based English textbook based on total physical response method for elementary school students - Agci Hikmawati; Rindu Handayani (Universitas Ahmad Dahlan)
This study aimed to develop and provide an enjoyable, meaningful, and cultural – based English textbook for elementary school students on the coast of Kurau village, Bangka Belitung Province. The observation and interview were undertaken to acknowledge the needs of the students in improving and advancing their understanding of English as well as to afford them an expedient textbook to be explored. Lee and Owens (2004) model has been used for this research and development study in designing the book. Total physical response method was also implemented in some exercises within the book to engage students’ attention and comprehension towards English learning. The data gathered in this study were collected through questionnaires, pre-test, and post-test. Based on the data analysis, the research finding shows that the cultural-based English textbook for elementary students is feasible. Feasibility obtained from the book was very good. Percentage of assessment by the content expert reached 82 % and the media expert was 87%. The calculation of T-paired test showed that there was a difference in learning achievement between the pre-test and the post-test score, which was 70.00 to 78.00 or increased 15%. Thus, there is an increasing score and this cultural – based textbook is effective to be used by the elementary students.